Visual screening in orthogeriatric rehabilitation setting: a single centre pilot study - Chi Kit Yan; Siraj Farid; Jay Chillala; Robert Harper (Clinical Medicine, 2025)
Introduction: Visual impairment is a prevalent issue among the older population, with studies suggesting approximately one in five individuals over the age of 75 experience some form of visual loss in the UK.1 As the population ages, this figure is expected to rise, with significant implications for health, independence and quality of life. One of the most critical consequences of visual impairment in older adults is its association with an increased risk of falls. Evidence suggests that impaired vision contributes significantly to postural instability, environmental misjudgment and delayed reaction times, all of which heighten the risk of falls.2,3Falls are a major cause of morbidity and mortality in older adults, and poor vision has been identified as a contributory factor in up to 30% of falls in the UK.4 Nevertheless, routine visual assessment is not typically integrated into medical or rehabilitation settings, particularly outside of specialist ophthalmic services.This pilot study explored the feasibility of bedside visual screening within an orthogeriatric rehabilitation unit, aiming to assess the feasibility for identification of unaddressed visual deficits and inform fall prevention strategies. Method: Eligible participants were aged ≥65 years, had sustained a fall before admission and scored greater than 6/10 on the Abbreviated Mental Test Score. Informed verbal consent was obtained. A resident doctor, trained by a consultant optometrist from Manchester Royal Eye Hospital, performed the assessments. These included: • Visual acuity testing was carried out using the Early Treatment Diabetic Retinopathy Study (ETDRS) LogMAR chart at 3 m under standard room lighting. Both unaided vision and pinhole visual acuity were recorded for each eye. • Visual fields and contrast sensitivity testing using Melbourne Rapid Fields (MRF), a validated web-based perimetry tool (Fig 1); • A detailed ocular history was taken, including spectacle use, date of last primary care optometry visit, and any existing ophthalmological follow-up or diagnoses.Electronic health records were reviewed to determine whether visual assessments had been documented by the admitting team. Results and Discussion: A total of 20 patients were recruited into the study over a 3-month period. LogMAR testing showed 35% of patients had vision worse than 0.3 (ie, 6/12 Snellen equivalent) in at least one eye, with pinhole testing suggesting refractive error in several cases. MRF contrast sensitivity assessment revealed reduced contrast acuity in 85% of patients, and 45% had abnormal visual field findings. Only 15% had any documented vision assessment by the admitting medical team despite admission caused by falls. Ocular histories highlighted poor spectacle adherence, limited ophthalmic follow-up and low engagement with optometric services; only 15% had attended a routine sight-test in the past year, despite being eligible for free sight-testing. Conclusion: Bedside visual screening in the orthogeriatric setting is both feasible and potentially clinical valuable. A high prevalence of undetected visual deficits suggests an overlooked yet modifiable risk factor for falls and rehabilitation outcomes. Standardised tools, such as LogMAR and MRF, used by trained non-specialists, can help identify vision issues early and support holistic fall prevention strategies. These findings lay the foundation for broader quality improvement work to integrate routine vision screening into